1994
DOI: 10.1002/dev.420270403
|View full text |Cite
|
Sign up to set email alerts
|

Influence of early life events on immune reactivity in adult mice

Abstract: The effects of postnatal manipulations on different immune parameters were investigated in adult female mice. Postnatal stress consisted of a 15-min daily exposure to clean bedding (temperature maintained at 35 degrees C) for the first 2 weeks of life in the absence of the mother but in the presence of littermates. Controls were unhandled until weaning. At 60 days of age, female mice stressed during postnatal development showed enhanced immune reactivity as assessed by NK-cell activity and T-cell mitogenesis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 23 publications
1
12
0
Order By: Relevance
“…A similar rebound has been observed in children recovering from stress (Doppman et al, 1986), and in mice injected with BCG (Meyer and Grundmann, 1980). In addition, and in line with previous studies that have indicated that some stress treatments may have immunopotentiating effects (Neveu et al, 1994), relative thymus weight showed an increase after the first stress session (Fig. 1); though note that severe stress is usually immunosuppressive Brosschot et al, 1994;Glaser and Kiecolt-Glaser, 1987;Keller et al, 1983;Pedersen et al, 1994;Schleifer et al, 1983).…”
Section: Non-programmed Changes In Thymussupporting
confidence: 82%
“…A similar rebound has been observed in children recovering from stress (Doppman et al, 1986), and in mice injected with BCG (Meyer and Grundmann, 1980). In addition, and in line with previous studies that have indicated that some stress treatments may have immunopotentiating effects (Neveu et al, 1994), relative thymus weight showed an increase after the first stress session (Fig. 1); though note that severe stress is usually immunosuppressive Brosschot et al, 1994;Glaser and Kiecolt-Glaser, 1987;Keller et al, 1983;Pedersen et al, 1994;Schleifer et al, 1983).…”
Section: Non-programmed Changes In Thymussupporting
confidence: 82%
“…Evidence that environmental manipulations in newborn rat pups may lead to persistent changes in the endocrine, immune, and behavioral reactivity of adult rats is mounting (39,42,43,45). Neonatally stressed adult rats have decreased exploratory behavior in novel environments, a lower threshold for learned helplessness, and increased loss of hippocampal neurons associated with early onset cognitive defects compared to control groups of adult rats (36,39,45).…”
Section: Discussionmentioning
confidence: 99%
“…5). Neonatal handling in mice enhances cell-mediated immune responses such as NK cell cytotoxicity and mitogen-induced lymphocyte proliferation in adult mice (30). In contrast, differences in immune responsiveness between handled and nonhandled rats were not as pronounced or have not been consistently observed for either antibody responses or predisposition to tumors (31,32).…”
Section: Postnatal Environment and Maternal Factorsmentioning
confidence: 94%